The Management of Guidance and Counseling Teachers in Addressing Student Delinquency at MTs Al-Iman Mukomuko - Pipi Yuniarti (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The objective of this study is to gain a comprehensive understanding of the dynamics of student delinquency at MTs Al-Iman Mukomuko and to examine the effectiveness of the efforts made by Guidance and Counseling (BK) teachers in addressing these issues. This research adopts a qualitative descriptive methodology. The subjects of the study include BK teachers, students, and related parties at MTs Al-Iman Mukomuko. Additional data collection methods used in this study are observation, interviews, documentation, and questionnaires. Data analysis involves data collection, reduction, presentation, and verification. The researcher acts as the primary instrument, supported by tools such as interview guidelines, observation sheets, and questionnaires. At MTs Al-Iman Mukomuko, guidance and counseling (BK) management has demonstrated positive results in addressing student delinquency. This indicates that the approaches employed by BK teachers are effective in dealing with various issues faced by students. However, this study also highlights that increasing parental involvement is crucial for the success of the BK program. Parents who actively participate in the guidance and counseling process can provide additional support to students, enhance their sense of care, and contribute to emotional stability. To achieve better outcomes, it is also essential to optimize available resources, including community support and facilities.